2001
DOI: 10.1557/jmr.2001.0481
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic cavitation as a tool to control macro-, micro-, and nano-properties of inorganic materials

Abstract: Hydrodynamic cavitation was shown to be a powerful tool for the synthesis of nanostructured catalysts, ceramics, and piezoelectrics in high phase purities. The macro-, micro-, and nano- properties of solid-state materials could be controlled through adjusting the cavitational regime during synthesis by simple mechanical adjustment. The synthesis of nanostructured titania, piezoelectrics, perovskites, supported and unsupported cobalt molybdates, and Pd and Ag supported on alumina illustrate changes in morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Research in the past two decades has demonstrated immense promise of hydrodynamic cavitation reactors for intensification of various physical and chemical processes such as degradation of dyes, 1 hydrolysis of oils, 2 degradation of recalcitrant pollutants and wastewater treatment, 3,4 nanosynthesis, 5,6 potable water disinfection, 7 and microbial cell disruption. 8,9 The literature on application of hydrodynamic cavitation for process intensification is quite vast and references cited above are only a few representative studies.…”
Section: Introductionmentioning
confidence: 99%
“…Research in the past two decades has demonstrated immense promise of hydrodynamic cavitation reactors for intensification of various physical and chemical processes such as degradation of dyes, 1 hydrolysis of oils, 2 degradation of recalcitrant pollutants and wastewater treatment, 3,4 nanosynthesis, 5,6 potable water disinfection, 7 and microbial cell disruption. 8,9 The literature on application of hydrodynamic cavitation for process intensification is quite vast and references cited above are only a few representative studies.…”
Section: Introductionmentioning
confidence: 99%
“…Although light emission from hydrodynamic cavitations was observed in the 1960's [4], the chemical effects of hydrodynamic cavitation have only been properly investigated since 1993 [5][6][7][8][9]. Hydrodynamic cavitation has been recently employed in the preparation of nanostructured materials [10,11], the removal of chemicals from wastewater treatment [12][13][14][15][16][17][18][19], water disinfection [20], and the degradation of polymers [21,22].Chlorocarbons consist of chloromethane, dichloromethane, chloroform, carbon tetrachloride, trichloroethylene, tetrachloroethylene, and 1,1,1-trichloroethane. Carbon tetrachloride and chloroform are among the most widespread contaminants in surface and underground water, and in tap water treated by chlorination.…”
mentioning
confidence: 99%
“…It was known that acoustic cavitation from sonication possibly produces a series of mechanochemical effects, such as high shear forces, micro-jets, shock wave and cavitation bubbles which are capable of inducing dramatic changes in product morphology [19,20]. In the current system under sonication, it was believed that high shear forces and cavitation bubbles created by sonication retarded the magnetic attraction between the prickly spheres and subsequent fusing growth and finally resulted in dispersed prickly spheres [21,22].…”
Section: Resultsmentioning
confidence: 99%